Sheep Farming An Approach to Feed, Growth and Health - Monteiro, António (IntechOpen, 2021)
This book examines the branch of animal husbandry of sheep farming. It focuses on sheep feeding in regions with extensive sheep farming, such as the Sahel region in Africa and Serra da Estrela, Portugal, and describes the form and importance of using natural resources. Chapters cover such topics as sheep feeding and digestion, how to improve carcass yield, and how technologies can help diagnose and study respiratory pathologies in sheep.